2021
DOI: 10.3390/ijerph18041836
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Consequences of COVID-19 Fear and the Moderator Effects of Individuals’ Underlying Illness and Witnessing Infected Friends and Family

Abstract: The COVID-19 virus has become a fearful epidemic for people all over the world. In Turkey, long quarantine periods and curfews have increased both physical and psychological problems. Due to the rapid spread and substantial impact of the COVID-19 virus, different psychological effects were observed among different segments of society, such as among young people, elderly people, and active workers. Because of fear caused by the COVID-19 virus, it is thought that depression, stress, and anxiety levels have incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
77
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(100 citation statements)
references
References 69 publications
9
77
1
2
Order By: Relevance
“…Moreover, dysregulation of the HPT axis can be a psychological impact of COVID-19 pandemic. Fear and stress in patients with COVID-19 can induce several mental problems, including anxiety, depression, post-traumatic stress disorder, and sleep disturbances (Koçak et al 2021 ). Recently, it was reported that survivors of COVID-19 showed anxiety disorder (19.15%) and psychotic disorders (2.77%) 6 months after recovery (Taquet et al 2021 ).…”
Section: Sars-cov-2 Effects On the Male Reproductive System: Pathologic Alterations And Underlying Mechanismsmentioning
confidence: 99%
“…Moreover, dysregulation of the HPT axis can be a psychological impact of COVID-19 pandemic. Fear and stress in patients with COVID-19 can induce several mental problems, including anxiety, depression, post-traumatic stress disorder, and sleep disturbances (Koçak et al 2021 ). Recently, it was reported that survivors of COVID-19 showed anxiety disorder (19.15%) and psychotic disorders (2.77%) 6 months after recovery (Taquet et al 2021 ).…”
Section: Sars-cov-2 Effects On the Male Reproductive System: Pathologic Alterations And Underlying Mechanismsmentioning
confidence: 99%
“…Due to infections and sudden deaths, individuals have felt rising COVID-19 fear. This fear has reduced reasoning and generated low-level quality of living (Koçak et al 2021b). It was seen that the resilience and quality of life decreased because of high COVID-19 fear (Karataş and Tagay 2021).…”
Section: H2c Depression Has a Negative Effect On Satisfaction With Lifementioning
confidence: 99%
“…Also, recent studies have revealed certain gender-based differences in the fear experienced in relation to the COVID-19 pandemic. Females have significantly reported higher levels of fear of COVID-19 ( Humer et al, 2020 ; Korukcu et al, 2020 ; Liu et al, 2020 ; Qiu et al, 2020 ; Reznik et al, 2020 ; Trnka and Lorencova, 2020 ; Tzur Bitan et al, 2020 ; Koçak et al, 2021 ; Pak et al, 2021 ), depression, anxiety, and stress ( Mazza et al, 2020 ) than males.…”
Section: Introductionmentioning
confidence: 99%